The Contribution of Student Activity and Learning Facilities to Learning Independency and its Impact on Mathematics Learning Outcomes in Junior High Schoo - Ainun Rahma Firdausy; Nining Setyaningsih; La Suha Ishabu; Mohamad Waluyo (Universitas Muhammadiyah Surakarta, 2019)
This study aims to: (1) examine the contribution of student activity and learning facilities to mathematical learning outcomes indirectly through learning independence, (2) examine the contribution of student activity and learning facilities to learning independence, (3) test the contribution of student learning independence to results learn math. This type of research is quantitative with the research subjects being all VII grade students of the Muhammadiyah Middle School Surakarta Special Program in 2018/2019. Data collection is done by questionnaire and documentation. The data analysis technique used is path analysis which has previously been carried out in five tests of data analysis prerequisites, namely: normality test with liliefors, linearity test, multicollinearity test, heteroscedasticity test and autocorrelation test. The results of the study with a significance level of 0.05, namely: (1) there is a contribution of student activity and learning facilities to learning outcomes indirectly through learning independence by 23.9%, (2) there is a contribution of student activity and learning facilities to learning independence by 64%, (3) there is a contribution of learning independence to mathematics learning outcomes of 15.68%.